Potential distribution of the citrus Mal Secco disease in the Mediterranean basin under current and future climate conditions. (21st December 2022) - Krasnov, Helena; Ezra, David; Bahri, Bochra A.; Cacciola, Santa O.; Meparishvili, Galina; Migheli, Quirico; Blank, Lior
Abstract: Species distribution models are widely used to estimate the potential geographic distribution of species habitat. They are also used to predict the impact of climate change on species distributions. In this study, we examined the distribution of Mal Secco disease, an infective disease of citrus caused by the fungus Plenodomus tracheiphilus . To model the Mal Secco distribution under current and two future (2050 and 2070) climatic scenarios in the Mediterranean basin, eight climate variables were incorporated into the Maximum Entropy (MaxEnt) model. All three model distributions had high AUC values (0.97), indicating excellent performance. The precipitation during the wettest month and the minimum temperature during the coldest month contributed the most to the model. The suitable areas for the Mal Secco disease were predicted to decrease by up to 23% by the year 2070. For each of the three scenarios, the change in the proportion of suitable areas along the longitudinal (west–east) and latitudinal (south–north) geographical axes of the Mediterranean basin showed a similar trend. Our study highlights the supposition that while climate change is likely to reduce the extent of suitable areas, no range shift is expected to occur in the Mediterranean basin. Abstract : A species distribution model showed that climate change is likely to reduce the extent of suitable areas for the Mal Secco citrus disease by up to 23% by the year 2070.